ANALYSIS OF ATTACHMENT IN THE FULFILLMENT OF RIGHTS FOR BREASTFEEDING FEMALE INMATES IN PRISONS - Lestari, Hafriah Dwi; Simanjuntak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
One of the rights fulfilled for breastfeeding female inmates is that inmates with children can care for them in prison until the child is 3 years old, in accordance with the Bangkok Rules, Law Number 22 of 2022, and related government regulations. Currently, the Palu Women's Prison is housing four infants of female inmates who are breastfeeding. Although the prison environment is less than ideal for a child's growth and development, this effort is important to maintain the bond between mother and child. This research aims to analyze the attachment patterns and the fulfillment of rights for breastfeeding female prisoners, as well as the obstacles they face at the Class III Women's Prison in Palu. This research uses a qualitative method where data collection is conducted through interviews and observations. Qualitative data analysis consists of data reduction, data presentation, and conclusion drawing. The results of this study show that there is no special treatment for nursing prisoners and their accompanying children. Nevertheless, a secure attachment between the mother and child remains formed. These inmate mothers continue to strive to meet their children's needs with the support of facilities provided by the prison authorities, although these facilities are also limited, such as the absence of healthcare personnel, lack of play areas, minimal breastfeeding facilities, low education levels among inmates, no special budget, and lack of knowledge about mother-child bonding. Keywords: Breastfeeding; Attachment; Women Prison